Asian and Pacific Coasts 2003:proceedings of the 2nd international conference : Makuhari, Japan, 29 February-4 March 2004 /Yoshimi Goda, Wataru Kioka, Kazuo Nadaoka - Goda, Yoshimi
Includes bibliographical references.